PURSE SEINE’S PROFILE OPERATED IN PANGANDARAN WATERS - Asri, Helmalia; Dewanti, Lantun Paraditha; Putra, Pringgo Kusuma Dwi Noor Yadi; Akbarsyah, Nora (Departemen PSP IPB, 2025)
Purse seine fishing gear is one of the active fishing gear widely used by fishermen in the waters of Pangandaran. The main target fish species for this fishing gear are black pomfret (Parastromateus niger), mackerel (Rastrelliger faughni), and skipjack tuna (Katsuwonus pelamis). This research refers to Ministerial Regulation No. 36 of 2023 to determine the profile of purse seine fishing gear in Pangandaran. The regulation discusses the placement of fishing gear and fishing aids in measured fishing zones and state fisheries management areas in inland waters. The research was conducted to determine the construction, specifications of fishing gear auxiliary equipment (ABPI) and vessels, as well as fishing routes for operating purse seine fishing gear in Pangandaran waters. The research was carried out from January to February 2025 at PP Cikidang and TPI Batukaras in Pangandaran District. The research was conducted using a descriptive method. A total of 30 samples were collected using the Slovin formula from both research sites. The research results indicate that the purse seine fishing gear in Pangandaran is locally known as tingkeran. The purse seine in Pangandaran has an upper rope length of 250–750 meters and a mesh size of 1.5–2 inches. The operation of this fishing gear is assisted by a 2 GT vessel equipped with an outboard motor as the propulsion system to navigate the fishing routes. Key words: exploratory, fishing area, mesh size, head rope